Iron Precursor Decomposition in the Magnesium Combustion Flame: A New Approach for the Synthesis of Particulate Metal Oxide Nanocomposites. (2nd August 2017) - Gheisi, Amir R.; Niedermaier, Matthias; Tippelt, Gerold; Lottermoser, Werner; Bernardi, Johannes; Diwald, Oliver
Abstract: Powders of Fe–Mg–O nanocomposite particles have been grown using a novel chemical vapor synthesis approach that employs the decomposition of a metalorganic precursor inside the metal combustion flame. After annealing in controlled gas atmospheres composition distribution functions, structure and phase stability of the obtained magnesiowüstite nanoparticles are measured with a combination of techniques such as inductively coupled plasma‐optical emission spectroscopy, energy dispersive X‐ray spectroscopy, X‐ray diffraction, and scanning and transmission electron microscopy. Complementary Mössbauer spectroscopy measurements reveal that depending on Fe loading and temperature of annealing either metastable and superparamagnetic solid solutions of Fe 3+ ions in periclase (MgO) or phase separated mixtures of MgO and ferrimagnetic magnesioferrite (MgFe2 O4 ) nanoparticles can be obtained. The described combustion technique represents a novel concept for the production of mixed metal oxide nanoparticles. Adressing the impact of selected annealing protocols, this study underlines the great potential of vapor phase grown non‐equilibrium solids, where thermal processing provides means to trigger phase separation and, concomitantly, the emergence of new magnetic properties. Abstract : Vapor‐phase‐grown composite metal oxide nanoparticle systems are non‐equilibrium solids. In this class of functional materials subsequent thermal processing can induce phase separation and the emergence of new magnetic phases.